2011
DOI: 10.1073/pnas.1013465108
|View full text |Cite
|
Sign up to set email alerts
|

Aphid genome expression reveals host–symbiont cooperation in the production of amino acids

Abstract: The evolution of intimate symbiosis requires the coordination of gene expression and content between the distinct partner genomes; this coordination allows the fusion of capabilities of each organism into a single integrated metabolism. In aphids, the 10 essential amino acids are scarce in the phloem sap diet and are supplied by the obligate bacterial endosymbiont ( Buchnera ), which lives inside specialized cells called bacteriocytes. Although Buchnera ’s genome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
492
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 365 publications
(510 citation statements)
references
References 38 publications
17
492
0
1
Order By: Relevance
“…This hypothesis has been somehow neglected so far (but see : Miller and Yellowlees, 1989;Wang and Douglas, 1998;Yellowlees et al, 2008) based on evidence that GS/GOGAT cycle, the fastest route for incorporating ammonium into amino acids through glutamate, is not widespread in animals. However, recent studies demonstrated that GS/GOGAT cycle is active in several metazoans (Scaraffia et al, 2005;Hansen and Moran, 2011) and our analyses using BLAST algorithm (Altschul et al, 1990) indicate that transcripts encoding proteins with high similarities to the domains of GOGAT are present in two cnidarian genomes (Nematostella vectensis (Sullivan et al, 2006), genBank accession number: XP_001630774.1; Acropora digitifera (Shinzato et al, 2011), http://marinegenomics.oist.jp/acropora _digitifera/, gene ID: aug_v2a.08445.t1; Supplementary Table S2). In congruence with the rapid 15 N-enrichment observed in the coral tissue by Single-cell view of ammonium assimilation in corals M Pernice et al NanoSIMS after the pulse of 15 N-ammonium enriched seawater, the results of these BLAST searches suggest that coral hosts could use GS/GOGAT cycle to rapidly fix seawater-derived ammonium into amino acids.…”
Section: Resultsmentioning
confidence: 99%
“…This hypothesis has been somehow neglected so far (but see : Miller and Yellowlees, 1989;Wang and Douglas, 1998;Yellowlees et al, 2008) based on evidence that GS/GOGAT cycle, the fastest route for incorporating ammonium into amino acids through glutamate, is not widespread in animals. However, recent studies demonstrated that GS/GOGAT cycle is active in several metazoans (Scaraffia et al, 2005;Hansen and Moran, 2011) and our analyses using BLAST algorithm (Altschul et al, 1990) indicate that transcripts encoding proteins with high similarities to the domains of GOGAT are present in two cnidarian genomes (Nematostella vectensis (Sullivan et al, 2006), genBank accession number: XP_001630774.1; Acropora digitifera (Shinzato et al, 2011), http://marinegenomics.oist.jp/acropora _digitifera/, gene ID: aug_v2a.08445.t1; Supplementary Table S2). In congruence with the rapid 15 N-enrichment observed in the coral tissue by Single-cell view of ammonium assimilation in corals M Pernice et al NanoSIMS after the pulse of 15 N-ammonium enriched seawater, the results of these BLAST searches suggest that coral hosts could use GS/GOGAT cycle to rapidly fix seawater-derived ammonium into amino acids.…”
Section: Resultsmentioning
confidence: 99%
“…Their genomes are fundamentally a subset of those of freeliving relatives, and the functional role of symbiosis is better explained by a metabolic cooperation between partners (28,29). An interesting exception are bacterial secretion systems (BSSs), which are probably involved in the ancestral invasion process and are often found in an active or degraded form in symbiont genomes (25).…”
Section: Resultsmentioning
confidence: 99%
“…Buchnera cells are located in the cytosol of specialized host cells called bacteriocytes, where each is enclosed in a host-derived membrane (4,(22)(23)(24). Host and symbiont functions must be coordinated to maintain an integrated system of nutrient biosynthesis and to ensure transmission to progeny, and some evidence supports host-control of the symbiosis (10,21,25). One might expect tight control of Buchnera numbers, given the essentiality of this symbiosis, but several reports suggest that regulation of the symbiosis is highly variable.…”
mentioning
confidence: 99%
“…Buchnera is found in almost all aphids and provisions hosts with essential amino acids that are lacking or rare in the diet of plant phloem sap (5,21,22). Buchnera cells are located in the cytosol of specialized host cells called bacteriocytes, where each is enclosed in a host-derived membrane (4,(22)(23)(24).…”
mentioning
confidence: 99%